Compressibility of compacted Bangkok clay - Prinya Sutabutra; Chai Muktabhant; Moh, Za-Chieh; Jones, John Hugh (Bangkok : SEATO Graduate School of Engineering, 1967)
Soil samples were collected from Bangkae district Bangkok, Thailand, at a depth of about one meter below ground surface. The physical properties of samples were evaluated. At selected dry densities and moisture contents, soil samples were compacted by three different methods: dynamic, static, and kneading compaction. The compacted examples were held at constant volume and immersed in distilled water, One-dimensional consolidation tests were conducted to determine the compressibility and consolidation of the compacted clay samples. The results of the experiments indicated that samples compacted by different methods at the same dry density and moisture content had different structures, different compressibilities, and different consolidation behavior. Methods of compaction which caused little shear strain during compaction resulted in a high degree of flocculation of the soil structure. Specimens prepared by static compaction, having a high degree of flocculated structure, were less compressible than specimens prepared by dynamic and kneading compaction. In the latter the pressure was not high enough to reduce the void space. No unique relationship was found to exist between the rate of consolidation and the method of compaction.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Thesis (M.Eng.) - SEATO Graduate School of Engineering, 1967
Keywords: Clay -- Thailand -- Bangkok